2018
DOI: 10.1353/aad.2018.0014
|View full text |Cite
|
Sign up to set email alerts
|

A Breast Cancer Education Program for D/deaf Women

Abstract: Barriers to obtaining breast cancer prevention knowledge and breast cancer screening have been noted among D/deaf women. A randomized controlled trial (RCT) is described that tested a culturally and linguistically tailored breast cancer education program conducted among a racially/ethnically diverse sample of 209 D/deaf women age 40 years or older. The study focused on D/deaf women with no more than a secondary education, a population at relatively high risk for incomplete breast health knowledge and services.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Access barriers, such as cost/lack of insurance, lack of transportation, and difficulty making an appointment, were also commonly reported across quantitative and qualitative studies [42,50,52,54,63,72,[74][75][76][77]. Additional barriers to mammography screening include concerns around radiation exposure, competing demands/time, and women not being aware of or told by their provider to get a mammogram [46,47,51,52,54,56,63,71,72,74,75,77]. Overall, perceived barriers represented a consistent group of drivers of mammography screening behavior, with women reporting more barriers being less likely to receive a mammogram [40, 42, 43, 45, 48•, 53, 61, 62, 66].…”
Section: Perceived Barriers To Mammography Screeningmentioning
confidence: 99%
“…Access barriers, such as cost/lack of insurance, lack of transportation, and difficulty making an appointment, were also commonly reported across quantitative and qualitative studies [42,50,52,54,63,72,[74][75][76][77]. Additional barriers to mammography screening include concerns around radiation exposure, competing demands/time, and women not being aware of or told by their provider to get a mammogram [46,47,51,52,54,56,63,71,72,74,75,77]. Overall, perceived barriers represented a consistent group of drivers of mammography screening behavior, with women reporting more barriers being less likely to receive a mammogram [40, 42, 43, 45, 48•, 53, 61, 62, 66].…”
Section: Perceived Barriers To Mammography Screeningmentioning
confidence: 99%
“…Key finding from this study concerns the effectiveness of the sign language training video for improving the BSE skills of deaf women. As explained above, hearing impaired women cannot benefit from healthcare services sufficiently, so they lack knowledge about BSE and cancer screening programs (Berman et al, 2013;Cumberland et al, 2018;Koçak et al, 2019), which are necessary for early diagnosis of breast cancer (Koçak et al, 2019). In Turkey, 60. while none of the participating hearing impaired women with a mean age of 50-61.7 years had done so.…”
Section: Resultsmentioning
confidence: 99%
“…For example, multiple interventional studies in our series conducted preintervention surveys and found that deaf adults consistently had statistically significant lower baseline scores for cancer-specific knowledge and were more likely to not understand the value of or recognize cancer-specific screening tests. 4,[11][12][13][14][15][16][17][18][19][20][21] In the most extreme example, a focus group interview study reported that a breast cancer survivor stated she did not know what cancer was when asked, despite being a survivor. 21 However, other variables, beyond deafness, may also be in play such as socioeconomic status, level of education, language preference, and so forth.…”
Section: Health Care Barriersmentioning
confidence: 99%
“…Moreover, those same studies showed that accessible programs can lead to better adherence to cancer-specific screening recommendations or avoidance of carcinogens such as tobacco use in deaf youth. 4,[11][12][13][14][15][16][17][18][19][20][21] The third barrier was deaf patients' frustration with the health care system and the lack of linguistically and culturally competent health care providers. A survey of ASL interpreters showed that multiple providers did not understand what effective communication with deaf patients entailed and thought inferior methods such as lipreading were acceptable forms of communication.…”
Section: Blinded Randomized Trialmentioning
confidence: 99%